Transcatheter Restoration of the Left Ventricular Outlet in a Patient With an Implanted Apicoaortic Conduit - Axel Unbehaun, MD; Ulrich Gerckens, MD; Christoph Klein, MD; Alexander Berger, MD; Mazen Alhaloush, MD; Jan Knierim, MD; Alexander Mladenow, MD; Natalia Solowjowa, MD; Volkmar Falk, MD; Joerg Kempfert, MD (JACC: Case Reports, 2020)
We describe the transcatheter management of severe aortic regurgitation in a middle-aged patient with a porcelain aorta who underwent implantation of an apicoaortic valved conduit 12 years ago. Instantaneous relief of heart failure symptoms was achieved by restoring antegrade blood flow to the ascending aorta. (Level of Difficulty: Advanced.)